Sexual Behavior in the Human Female - Kinsey, Alfred C. (Alfred Charles), 1894-1956 (Book collections on Project MUSE., 1998)
"Sexual Behavior in the Human Female was originally published in 1953, five years after the male volume. The material presented in this book was derived from personal interviews with nearly 6,000 women and from studies in sexual anatomy, physiology, psychology, and endocrinology." "The book presents data on the incidence and frequency with which women participate in various types of sexual activity. The authors show how factors such as age, decade of birth, and religious adherence are reflected in patterns of sexual behavior. Some measure of the social significance of the various types of sexual behavior is provided. The authors make comparisons of female and male sexual activities and investigate the factors which account for the similarities and differences between female and male patterns of behavior."--Jacket